Prognostic Indices for Predicting Facial Nerve Outcome following the Resection of Large Acoustic Neuromas - Grahnke, Kurt; Garst, Jonathan R.; Martin, Brendan; Leonetti, John P.; Anderson, Douglas E. (Journal of Neurological Surgery Part B: Skull Base, 2017)
This study analyzes the simple ratio of anterior-to-posterior extension of large (>2.5 cm) acoustic neuromas relative to the internal auditory canal (ICA; anterior–posterior [A/P] index) as a tool for predicting risk of facial nerve (FN) injury. In total, 105 patients who underwent microsurgical resection for large acoustic neuromas were analyzed retrospectively. House–Brackmann (HB) scores were assessed immediately postoperatively, at 1 month, and at 1 year. Lateral–medial, inferior–superior, A/P, and maximum diameters were measured from preoperative magnetic resonance images. These measurements and the A/P index were analyzed using univariable and multivariable statistical models to assess relationship to FN outcomes. The retrosigmoid, translabyrinthine, and combined approaches were used, and the extent of resection was evaluated. For every 1 standard deviation increase in the A/P index, a patient was 3.87 times more likely have a higher postoperative HB score (p < 0.0001). Accordingly, for every 1-mm increase anterior to the IAC, a patient was 16% more likely have a higher postoperative HB score (p < 0.001). After controlling for tumor size, a patient was still 3.82 times more likely have a higher postoperative HB score for every 1 standard deviation increase in the A/P index (p < 0.0001). While larger tumor size trended toward worse postoperative HB scores, it was not statistically significant. Our prognostic index may be useful to assess the risk of FN injury preoperatively for large acoustic neuromas, while also providing information about the tumor–nerve relationship.
Keywords: prognostic index; facial nerve outcomes; acoustic neuroma; vestibular schwannoma